Optimalisasi Gerakan Remaja Sehat: Pencegahan dan Penanggulangan Anemia melalui Intervensi Gizi - Prautami, Erike Septa; Harwanto, Fatria; Lumbantoruan, Santa Maria (Forum Kerjasama Pendidikan Tinggi, 2025)
Adolescence is a transitional phase from childhood to adulthood, marked by physical, psychological, and psychosocial changes. One of the most common health issues faced by adolescents, especially adolescent girls, is anemia. The low level of knowledge among adolescent girls about anemia and the underutilization of available land are the primary problems addressed in this community service activity. The aim of this program is to increase adolescent girls' knowledge about nutrition and anemia, as well as to utilize unused land to establish a dragon fruit garden. The purpose of this community service activity is to increase the knowledge of young women regarding anemia, utilize the existing land to create a dragon fruit garden where dragon fruit can be used to prevent anemia and install posters and distribute leaflets about nutrition and anemia. The methods used include socialization, education, training, and practical implementation of a dragon fruit garden using a drip irrigation system. The results of the activity showed a significant improvement in the participants' knowledge. Initially, 53 participants were categorized as having poor knowledge, but after the educational intervention, this number dropped to zero. Additionally, the number of participants with good knowledge increased from 2 to 48. Therefore, this activity has had a positive impact in raising awareness and enhancing adolescent girls' understanding of the importance of nutrition and anemia prevention.